Sludge-based premixed mortar and preparation method thereof
Through the preparation of sludge-based premixed mortar, the use of sludge-based admixtures and modified fiber fillers and other components, the mechanical properties and resource utilization of the mortar are improved, and the problem of insufficient performance of sea sludge treatment and premixed mortar is solved, so as to achieve High added value utilization and environmental benefits of waste resources.
Patent Information
- Application Number
- CN202411256174.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-31
AI Technical Summary
In the prior art, the construction of sea silt treatment facilities is lagging behind and the silt resources cannot be effectively utilized, resulting in environmental pollution and waste of resources. The ready-mixed mortar has shortcomings in mechanical properties, fluidity, water retention, settling time, and frost resistance.
The sludge-based premixed mortar is used to improve the compressive strength and flexural strength of the mortar through the synergistic effect of components such as cement, sludge-based blending materials, fine aggregates, modified fiber fillers, exciters and high-efficiency water reducers. Setting time, water retention rate and freezing resistance, and sludge powder and nickel slag are modified through ball milling and sintering processes to achieve high added value utilization of waste resources.
The resource utilization of waste resources such as sea silt, nickel slag and coal gangue has been achieved, which has reduced the cost of mortar production, improved the durability and stability of mortar, shortened the solidification time, and is in line with the concept of green and environmental protection development.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of construction engineering materials, and in particular to a silt-based premixed mortar and a preparation method thereof. Background Art
[0002] In recent years, as the construction of ecological civilization has risen to the national strategic level, more and more environmental protection projects have been put into implementation, among which water environment governance and ecological restoration are very important. Since 2022, Xiamen has thoroughly implemented and formulated a work plan for the battle against pollution, implemented various work tasks, and maintained the ecological environment quality at the forefront of the country. It has actively promoted coastline protection and comprehensive ecological improvement, and there is no black and smelly water in the urban built-up area. In 2023, Xiamen will implement rectification and improvement work on the ecological environment of Xinglin Bay. It will be rectified by adopting an environmental dredging combined with an ecological restoration plan. The sludge removed will be used by building bird habitats, in-situ ecological restoration, and raising the height of the sports island, further improving the ecological environment of the Xinglin Bay improvement area. It is worth noting that the sludge in Xinglin Bay is only utilized through internal consumption, and the sludge is not used for multiple resource utilization. It can be seen that my country's river sludge and sea mud collection, treatment and harmless treatment capabilities need to be enhanced. At present, there is still a problem of "heavy water and light mud". The construction of sludge treatment facilities is generally lagging behind, and the level of harmless treatment and resource utilization is not high. It is still in the initial growth stage. With the country's emphasis on ecological restoration and urban black and odorous water treatment, large-scale ecological dredging projects have been carried out, resulting in a huge increase in sludge production. The problem with marine sludge dumping today is that as sludge gradually increases, sludge pollution is also increasing year by year, and the offshore sludge dumping capacity is close to saturation. [ Through large-scale and wide-ranging dredging projects, water quality can be effectively improved, water environmental capacity can be expanded, and water supply safety for citizens can be guaranteed. However, if silt is not properly treated and disposed of, the secondary pollution caused by silt to the environment will seriously violate the original intention and purpose of clean production and further endanger the long-term development of mankind. Therefore, it is urgent to find a reasonable and scientific way to treat and dispose of marine silt.
[0003] With the development of science and technology, premixed mortar, as a new type of building material, green building material, and low-carbon material, has a lower emission rate of wastewater and waste gas in the production process, which meets the national requirements for the development of green building materials. At the same time, it shoulders the important mission of comprehensive utilization and recycling of industrial resources. According to statistics, the annual new construction area in my country is about 2 billion square meters, and the demand for building mortar should be 350-600 million tons. At present, the output of mortar is only 5% of the demand. Compared with premixed mortar, some commonly used special mortars such as wall and floor tile adhesives and interface treatment agents have industry standards, and their production and application are relatively mature. However, the commercialization process of premixed mortar is relatively slow. Most of the masonry and plastering mortars used on construction sites are still mixed on site, and the quality cannot be guaranteed, which is easy to have adverse effects on the construction quality and the surrounding environment. At present, the mechanical properties, fluidity, water retention, setting time, and antifreeze properties of premixed mortar need to be improved. Summary of the invention
[0004] The purpose of this application is to provide a silt-based premixed mortar and a preparation method thereof in view of the deficiencies of the current technology. The silt-based premixed mortar prepared in this application has the advantages of simple preparation, low cost, green environmental protection, etc., and has good compressive strength, flexural strength, setting time, water retention rate and antifreeze performance. It realizes the large-scale treatment and high value-added utilization of waste resources such as sea silt, nickel slag and coal gangue, truly realizes energy conservation and emission reduction and green circular development in the resource process of sea silt, nickel slag and coal gangue, can effectively reduce the production cost of mortar and is beneficial to environmental protection.
[0005] In the first aspect, the present application provides a silt-based premixed mortar, which adopts the following technical solution: A silt-based premixed mortar comprises the following raw materials, measured by weight: 200-250 parts of cement, 500-550 parts of silt-based admixture, 400-450 parts of fine aggregate, 12-15 parts of modified fiber filler, 5-6 parts of activator, 8-12 parts of high-efficiency water reducing agent and 120-150 parts of water.
[0006] By adopting the above technical solutions, cement provides basic bonding and forms the skeleton structure of mortar. It works together with silt-based admixtures to generate more cementitious substances through hydration reaction, thereby improving the compressive strength and flexural strength of mortar. Silt-based admixtures replace part of cement, reduce cement dosage and reduce costs; at the same time, they provide additional active ingredients to promote hydration reaction. Fine aggregate provides the particle structure required for mortar, increases the density and wear resistance of mortar. It works together with modified fiber fillers to improve the internal structure of mortar and reduce the risk of cracking. Modified fiber fillers enhance the toughness and crack resistance of mortar. The activator accelerates the hydration reaction, promotes the early strength development of concrete, and shortens the setting time. The high-efficiency water reducer reduces the water demand in mortar, improves the workability of concrete and reduces cracks. Water, as a basic component in the preparation of mortar, participates in the hydration reaction, affects the workability, setting time and final performance of mortar. In short, the synergistic effect of these components not only improves the performance of silt-based premixed mortar, but also realizes the effective utilization of waste resources, which is in line with the development concept of green environmental protection.
[0007] Preferably, the sludge-based admixture is composed of sludge powder and coal gangue in a mass ratio of 8:2 and is prepared by modification.
[0008] Preferably, the modification method of the sludge-based admixture comprises the following steps: S31, according to the mass parts, put 20 parts of ammonium bicarbonate, 30 parts of ammonium sulfate, 1 part of alkylphenol polyoxyethyl ether and 2 parts of graphene into a ball mill for ball milling, the ball milling speed is 80-100r / min, the ball milling time is 15-20min, and a mixture A is obtained; S32, according to the mass parts, put 800 parts of sludge powder and 200 parts of coal gangue into a ball mill for ball milling, the ball milling speed is 80-100r / min, the ball milling time is 30-40min, and a mixture B is obtained; S33, putting mixture A and mixture B into a ball mill for ball milling, the ball milling speed is 80-100r / min, the ball milling time is 20-25min, and a sludge-based admixture is obtained.
[0009] By adopting the above technical scheme, the modification method of sludge-based admixture involves multiple steps, aiming to improve the activity and cementing properties of sludge powder and coal gangue. S31: Prepare mixture A, and mix ammonium bicarbonate, ammonium sulfate, alkylphenol polyoxyethyl ether and graphene evenly through ball milling to facilitate subsequent reaction with sludge powder and coal gangue. Ammonium sulfate provides NH4+ ions to promote the depolymerization of glass and RO phase in sludge; ammonium bicarbonate can decompose to produce CO2 microcapsules to solve the problem of sludge stability; alkylphenol polyoxyethyl ether acts as a surfactant to improve the dispersibility and reactivity of the mixture; graphene promotes excitation reaction and accelerates hydration reaction. 32: Prepare mixture B, and mix sludge powder and coal gangue evenly through ball milling to improve its specific surface area and reaction activity. The combination of sludge powder and coal gangue makes mixture B have higher activity and cementing properties in mortar; ball milling increases the fineness of the mixture, which is conducive to the subsequent reaction with mixture A. S33: Prepare sludge-based admixtures, and ball-mill mixture A and mixture B again to make them fully react and mix to form the final sludge-based admixtures. Ammonium sulfate, ammonium bicarbonate, alkylphenol polyoxyethyl ether and graphene in mixture A work together with sludge powder and coal gangue in mixture B to improve the activity and cementing properties of sludge-based admixtures; ball milling further increases the fineness and uniformity of the admixtures, which is conducive to better performance in mortar. The role of sludge-based admixtures: replace part of the cement and reduce costs; provide additional active ingredients to promote hydration reactions; improve the compressive strength, flexural strength and water retention of mortar. Silt-based admixtures work together with other components such as cement, activators, modified fiber fillers, etc. to generate more cementitious substances through hydration reactions, thereby improving the overall performance of mortar; at the same time, large-scale treatment and high value-added utilization of waste resources such as sea sludge, nickel slag and coal gangue are realized, which is in line with the development concept of green environmental protection.
[0010] Preferably, the sludge powder has a particle size of 0.075-2 mm and accounts for 75-85% of the mass fraction of the coal gangue; the particle size of 2-6 mm accounts for 15-25% of the mass fraction of the coal gangue; and the particle size of 0.5-1 mm accounts for 15-25% of the mass fraction of the coal gangue.
[0011] Preferably, the method for preparing the sludge powder comprises the following steps: S51. Add 50 parts of sea silt into a stirrer according to the mass fraction, adjust the pH value of the sea silt to 3-4 with 1 mol / L hydrochloric acid solution, then add 18 parts of hydrogen peroxide with a mass concentration of 30%, and then add 80 parts of ferrous sulfate heptahydrate, stir evenly, and react for 10-20 minutes to obtain a mixture A; S52, adjusting the pH value of the mixture A to 6.5-7 using a 3 mol / L NaOH solution, transferring the mixture to a diaphragm plate and frame filter press for filtration until the water content of the sea silt is 55%, thereby obtaining sea silt with a water content of 55%; S53, adding 10 parts by mass of rice husk ash to sea silt having a water content of 55%, stirring evenly and then double-roll crushing to obtain slurry A, and drying slurry A at 100° C. for 6-8 hours to obtain mixture B; S54. According to the mass fraction, mix B is placed in a rotary kiln, pre-sintered at 500°C for 20 minutes, then heated to 900-1000°C, sintered for 3-4 hours, cooled to room temperature, ball-milled and sieved to obtain continuous graded silt powder with a particle size of 0.075-2mm and fine silt powder with a particle size of less than 0.075mm.
[0012] By adopting the above technical scheme, the preparation method of silt powder involves multiple steps, aiming to improve the volcanic ash activity of sea silt so that it can perform better in mortar. S51: Prepare mixture A, and pre-treat the sea silt by adjusting the pH value and adding hydrogen peroxide and ferrous sulfate heptahydrate to improve its chemical properties and reactivity. The hydrochloric acid solution adjusts the pH value to 3-4, which is conducive to the decomposition of hydrogen peroxide and the dissolution of ferrous sulfate; hydrogen peroxide plays an oxidizing role and promotes the decomposition of organic matter in sea silt; ferrous sulfate heptahydrate acts as a reducing agent to participate in the chemical reaction in the sea silt and improve its chemical properties. S52: Press filter the sea silt, and reduce the water content of the sea silt by pressing filter, so as to provide suitable moisture conditions for subsequent treatment. The NaOH solution adjusts the pH value to 6.5-7 to provide a suitable alkaline environment for the stabilization of the sea silt; the pressing process effectively reduces the water content of the sea silt, which is conducive to the subsequent mixing and reaction with rice husk ash. S53: Prepare slurry A and mixture B, mix rice husk ash with sea silt with a water content of 55%, and then dry and crush to obtain a uniform mixture B. Rice husk ash is rich in silicon dioxide and aluminum oxide. It can enhance the volcanic ash activity of silt powder by sintering with sea silt. Even stirring and double-roll crushing ensure the full mixing of rice husk ash and sea silt, which is beneficial to the subsequent sintering reaction. S54: Sintering and ball milling screening, through rotary kiln sintering and ball milling screening, silt powder with high volcanic ash activity is obtained. Pre-sintering and high-temperature sintering processes promote the chemical reaction between rice husk ash and sea silt, forming more active SiO2 and active A12O3; ball milling and screening processes ensure the fineness and uniformity of silt powder, which is beneficial to better performance in mortar. The role of silt powder: as the main component of silt-based admixtures, it replaces part of cement and reduces costs; at the same time, it provides active ingredients, promotes hydration reaction, and improves the performance of mortar. Silt powder works together with other components such as cement, activator, modified fiber filler, etc. to generate more cementitious substances through hydration reaction, thereby improving the overall performance of the mortar; at the same time, it realizes the high added value utilization of waste resources such as sea silt, nickel slag and coal gangue, which is in line with the development concept of green and environmental protection.
[0013] Preferably, the fine aggregate is composed of modified fine nickel slag and fine silt powder in a mass ratio of 2:6, and the fine silt powder is the fine silt powder with a particle size of less than 0.075 mm prepared according to claim 5.
[0014] Preferably, the preparation method of the modified fine nickel slag is: according to the mass fraction, 10 parts of polyacrylic acid emulsion with a solid content of 20% is sprayed onto the surface of 1200 parts of fine nickel slag and stirred for 30-40 minutes, ball milled and sieved to obtain modified fine nickel slag with a particle size of 0.075mm-0.6mm and continuous gradation.
[0015] By adopting the above technical scheme, the preparation method of modified fine nickel slag involves multiple steps, aiming to improve the performance of fine nickel slag and make it play a better role in mortar. By spraying polyacrylic acid emulsion, the surface properties of fine nickel slag are improved, and its compatibility and reactivity with other components of mortar are improved. Polyacrylic acid emulsion has good film-forming and bonding properties, and can form a thin film on the surface of fine nickel slag to improve its bonding properties with cement and other fillers; at the same time, the water absorption and water retention properties of polyacrylic acid emulsion are conducive to internal maintenance and promote the water balance inside the mortar. By stirring and ball milling, it is ensured that the polyacrylic acid emulsion is evenly covered on the surface of fine nickel slag, and its fineness and uniformity are improved by mechanical action. Stirring fully mixes the polyacrylic acid emulsion with fine nickel slag, and ball milling further refines the particles, increases the specific surface area of fine nickel slag, and improves its reactivity and cementing ability. By screening, modified fine nickel slag with consistent particle size is obtained to meet the particle size requirements of mortar. Screening ensures that the particle size distribution of modified fine nickel slag meets the requirements, which is conducive to forming a tighter structure in the mortar and improving the overall performance of the mortar. Modified fine nickel slag: As part of the fine aggregate, it improves the internal curing effect of the mortar, improves the workability and setting time of the mortar; at the same time, its enhanced interface strength helps to improve the compressive strength and flexural strength of the mortar. The modified fine nickel slag works together with other components such as sludge-based admixtures and activators to generate more cementitious substances through hydration reaction and physical filling effect, thereby improving the overall performance of the mortar; at the same time, it realizes the high added value utilization of waste resources, which is in line with the development concept of green environmental protection.
[0016] Preferably, the preparation method of the modified fiber filler is as follows: 100 parts of carbon fibers with a length of 3-5 mm and 200 parts of pure water are mixed evenly, the temperature is raised to 35° C., ozone is introduced into the solution at a rate of 3 L / min for 35 minutes, and then the ozone supply is stopped; the solution is sealed, heated to 64° C., and allowed to stand for 4 hours; the solution is stirred for 25 minutes in an open state, 20 parts of 3-aminopropyltriethoxysilane ethanol solution with a mass concentration of 5% is added, the solution is heated to 50° C. and stirred for 50 minutes, and then 10 parts of nano-titanium dioxide with a particle size of 50 nanometers is added, stirred for 30 minutes, the nano-titanium dioxide is coated on the surface of the carbon fiber, filtered, rinsed with water 3 times, and vacuum dried at 80° C. to obtain the modified fiber filler.
[0017] By adopting the above technical scheme, the preparation method of the modified fiber filler involves multiple steps, including ozone treatment, heating, stirring and surface modification, and finally obtains modified carbon fibers with specific functions. The interface strength between carbon fibers and other components of the mortar is enhanced by surface modification of 3-aminopropyltriethoxysilane and titanium dioxide. This enhanced interfacial interaction helps to improve the overall mechanical properties of the mortar, including compressive strength and flexural strength. The modified carbon fiber filler has good photocatalytic ability, which may help to improve certain properties of the mortar, such as promoting the decomposition of harmful substances through photocatalytic reactions, thereby improving the environmental performance of the mortar. The good compatibility of the modified carbon fibers ensures that they can be evenly dispersed in the mortar matrix and avoid agglomeration problems, which is crucial to improving the mechanical properties of the mortar. The synergistic effect of the modified carbon fibers and other components (such as activators, high-efficiency water reducers, modified sludge-based admixtures, etc.) jointly improves the overall performance of the mortar, including compressive strength, flexural strength, water retention and frost resistance. In summary, the role of modified fiber fillers in mortar is mainly reflected in improving interface strength, providing photocatalytic ability and good compatibility, and synergizing with other components to jointly improve the overall performance of mortar. These characteristics make modified fiber fillers one of the key components to improve mortar performance.
[0018] Preferably, the cement is ordinary Portland cement of grade P·O42.5; the high-efficiency water reducing agent is a polyhydroxy acid-based high-efficiency water reducing agent, and the water reducing rate is 30%.
[0019] Preferably, the activator is prepared by mixing calcium hydroxide and sodium hydroxide in a mass ratio of 4:3.
[0020] By adopting the above technical solution, the activator plays a role in accelerating the hydration reaction in concrete, thereby promoting the early strength development of concrete and shortening the setting time. This feature is crucial to improving construction efficiency and accelerating project progress. Calcium hydroxide, as part of the activator, can increase the alkalinity in concrete, which is conducive to promoting the hydration reaction rate of minerals in cement, thereby improving the early strength of concrete. Sodium hydroxide can react with silicates in cement to form gelling substances, which can accelerate the solidification process of concrete and further improve the early strength and durability of concrete. Synergistic and complementary effects between calcium hydroxide and sodium hydroxide: calcium hydroxide mainly provides an alkaline environment to promote the hydration reaction, while sodium hydroxide accelerates the formation of gelling substances by reacting with silicates in cement. The combination of the two makes the hydration reaction more complete and generates more hydration products. Accelerate the formation of silicates and calcium compounds: through the synergistic effect of calcium hydroxide and sodium hydroxide, the activator can promote the hydration reaction in cement more quickly, accelerate the formation of silicates and calcium compounds, and form more hydration products, thereby improving the strength and early hardening speed of concrete. Improve engineering construction efficiency: This synergistic effect helps shorten the setting time of concrete, reduce waiting time, and improve the overall engineering construction efficiency, which is of great significance for the timely completion and cost control of engineering projects. In summary, the activator prepared by mixing calcium hydroxide and sodium hydroxide in a mass ratio of 4:3 plays a key role in the preparation of silt-based premixed mortar. Through its synergistic effect, the performance of the mortar is significantly improved, and the high added value of waste resources such as sea silt, nickel slag and coal gangue is realized, while reducing production costs and protecting the environment.
[0021] In a second aspect, the present application provides a method for preparing silt-based premixed mortar, which adopts the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned silt-based premixed mortar, comprising the following steps: first, according to the mass proportions, mix cement, modified fiber filler, high-efficiency water reducer and water evenly, then add silt-based admixtures and fine bones in sequence, stir evenly, and obtain silt-based premixed mortar.
[0022] In summary, the beneficial technical effects of this application are: 1. Resource utilization: By using waste resources such as sea silt, nickel slag and coal gangue as raw materials for mortar, large-scale processing and high value-added utilization of these resources are achieved, reducing environmental pollution and resource waste.
[0023] 2. Energy saving and emission reduction: The resource utilization process of sea silt, nickel slag and coal gangue realizes energy saving and emission reduction and green circular development, and reduces energy consumption and carbon emissions in the mortar production process.
[0024] 3. Cost reduction: Using industrial waste residue as raw material effectively reduces the production cost of mortar and reduces the cost of environmental pollution control.
[0025] 4. Performance improvement: The use of silt-based admixtures and modified fiber fillers improves the compressive strength, flexural strength, water retention and frost resistance of the mortar, making the mortar more durable and stable.
[0026] 5. Shortened setting time: The use of activators accelerates the hydration reaction, promotes the early strength development of concrete, shortens the setting time and improves construction efficiency.
[0027] 6. Environmental benefits: The entire preparation process complies with the development concept of green environmental protection and is conducive to the sustainable development of the building materials industry.
[0028] 7. Improved construction performance: The addition of ammonium sulfate and ammonium bicarbonate solves the problem of sludge stability and improves the safe use performance of the mortar; the water retention performance of polyacrylic acid polymer improves the internal maintenance of the mortar, which is beneficial to moisture balance and the reaction of fine nickel slag.
[0029] 8. Enhanced interface strength: Polyacrylic acid modified fine nickel slag and 3-aminopropyltriethoxysilane and titanium dioxide modified carbon fiber filler enhance the interface strength between the filler and other components of the mortar, and improve the overall performance of the mortar.
[0030] 9. Enhanced volcanic ash activity: Adding rice husk ash to sea silt and sintering them together increases chemical components such as silicon dioxide and aluminum oxide, which is beneficial to the enhancement of the volcanic ash activity of the silt powder and improves the reactivity and stability of the mortar. DETAILED DESCRIPTION
[0031] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0032] In the following examples, preparation examples and comparative preparation examples, 1 part means 1 kg.
[0033] The sea silt used in the preparation examples and embodiments comes from the Xiamen sea area (water content is 83%). The main components of the dry matter of the sea silt (the remaining material after drying at 105° C. to constant weight is the dry matter) are shown in Table 1 below: Table 1 Dry matter composition of sea silt The main chemical components of nickel slag in the preparation examples and embodiments are shown in Table 2 below: Table 2 Main chemical composition of nickel slag The main chemical components of the coal gangue in the preparation examples and embodiments are shown in Table 3 below: Table 3 Main chemical components of coal gangue Preparation Example 1 Preparation of silt powder and fine silt powder with a particle size less than 0.075 mm The method for preparing sludge powder comprises the following steps: S51. According to the weight ratio, 50 parts of sea silt were added into a stirrer, the pH value of the sea silt was adjusted to 3.5 with 1 mol / L hydrochloric acid solution, and then 18 parts of hydrogen peroxide with a weight concentration of 30% and 80 parts of ferrous sulfate heptahydrate were added, and the mixture was stirred evenly and reacted for 15 minutes to obtain a mixture A; S52, adjusting the pH value of the mixture A to 6.7 using a 3 mol / L NaOH solution, transferring the mixture to a diaphragm plate and frame filter press for filtration until the water content of the sea silt is 55%, thereby obtaining sea silt with a water content of 55%; S53, adding 10 parts by mass of rice husk ash to sea silt having a water content of 55%, stirring evenly and then double-roll crushing to obtain slurry A, and drying slurry A at 100° C. for 7 hours to obtain mixture B; S54. According to the mass fraction, mix B is placed in a rotary kiln, pre-sintered at 500°C for 20 minutes, then heated to 950°C and sintered for 3.5 hours, cooled to room temperature, ball-milled and sieved to obtain continuous graded silt powder with a particle size of 0.075-2mm and fine silt powder with a particle size of less than 0.075mm.
[0034] Preparation Example 2 Preparation of sludge-based admixture The modification method of sludge-based admixture comprises the following steps: S31, according to the mass parts, put 20 parts of ammonium bicarbonate, 30 parts of ammonium sulfate, 1 part of alkylphenol polyoxyethyl ether and 2 parts of graphene into a ball mill for ball milling, the ball milling speed is 90r / min, the ball milling time is 17min, and a mixture A is obtained; S32, according to the mass fractions, 800 parts of sludge powder and 200 parts of coal gangue were put into a ball mill for ball milling, the ball milling speed was 90r / min, and the ball milling time was 35min, to obtain a mixture B, wherein the sludge powder was the continuous graded sludge powder prepared in Preparation Example 1 with a particle size of 0.075-2mm; the coal gangue had a particle size of 2-6mm accounting for 75-85% by mass, and a particle size of 0.5-1mm accounting for 15-25% by mass; S33, putting mixture A and mixture B into a ball mill for ball milling, the ball milling speed is 90r / min, the ball milling time is 23min, and a sludge-based admixture is obtained.
[0035] Preparation Example 3 Preparation of modified fine nickel slag The preparation method of modified fine nickel slag is as follows: according to the mass fraction, 10 parts of polyacrylic acid emulsion with a solid content of 20% is sprayed onto the surface of 1200 parts of fine nickel slag and stirred for 35 minutes, ball milled and sieved to obtain modified fine nickel slag with a particle size of 0.075mm-0.6mm and continuous gradation.
[0036] Preparation Example 4 Preparation of modified fiber filler The preparation method of the modified fiber filler is as follows: 100 parts of carbon fibers with a length of 3-5 mm and 200 parts of pure water are mixed evenly, the temperature is raised to 35° C., ozone is introduced into the solution at a speed of 3 L / min for 35 minutes, and then the ozone supply is stopped; the solution is sealed, heated to 64° C., and allowed to stand for 4 hours; the solution is stirred for 25 minutes in an open state, 20 parts of 3-aminopropyltriethoxysilane ethanol solution with a mass concentration of 5% is added, the solution is heated to 50° C. and stirred for 50 minutes, and then 10 parts of nano-titanium dioxide with a particle size of 50 nanometers is added, and the mixture is stirred for 30 minutes, the nano-titanium dioxide is coated on the surface of the carbon fiber, filtered, rinsed with water 3 times, and vacuum dried at 80° C. to obtain the modified fiber filler.
[0037] Preparation of Comparative Example 1 Preparation of sludge powder The same as Preparation Example 1, except that, S53, according to the mass fraction, 0 parts of rice husk ash is added to the sea silt with a water content of 55%, and the mixture is evenly stirred and then double-rolled to obtain slurry A, and slurry A is dried at 100°C for 7 hours to obtain mixture B.
[0038] Preparation Comparative Example 2 The same as Preparation Example 2, except that the sludge powder is the continuously graded sludge powder with a particle size of 0.075-2 mm prepared in Preparation Example Comparative 1.
[0039] Example 1 A silt-based premixed mortar comprises the following raw materials by weight: 200 parts of cement, 500 parts of silt-based admixture, 400 parts of fine aggregate, 12 parts of modified fiber filler, 5 parts of activator, 8 parts of high-efficiency water reducer, and 120 parts of water, wherein the fine aggregate is composed of modified fine nickel slag and fine silt powder in a weight ratio of 2:6, the cement is P·O42.5 grade ordinary Portland cement, the high-efficiency water reducer is a polyhydroxy acid-based high-efficiency water reducer with a water reduction rate of 30%, and the activator is prepared by mixing calcium hydroxide and sodium hydroxide in a weight ratio of 4:3; The preparation method of the above-mentioned silt-based premixed mortar comprises the following steps: firstly, according to the mass proportions, cement, modified fiber filler, high-efficiency water reducing agent and water are uniformly mixed, and then silt-based admixtures and fine bones are added in sequence, and stirred evenly to obtain silt-based premixed mortar.
[0040] Example 2 A silt-based premixed mortar, comprising the following raw materials by weight: 250 parts of cement, 550 parts of silt-based admixture, 450 parts of fine aggregate, 15 parts of modified fiber filler, 6 parts of activator, 12 parts of high-efficiency water reducer, and 150 parts of water, wherein the fine aggregate is composed of modified fine nickel slag and fine silt powder in a weight ratio of 2:6, the cement is P·O42.5 grade ordinary Portland cement, the high-efficiency water reducer is a polyhydroxy acid-based high-efficiency water reducer with a water reduction rate of 30%, and the activator is prepared by mixing calcium hydroxide and sodium hydroxide in a weight ratio of 4:3; The preparation method of the above-mentioned silt-based premixed mortar comprises the following steps: firstly, according to the mass proportions, cement, modified fiber filler, high-efficiency water reducing agent and water are uniformly mixed, and then silt-based admixtures and fine bones are added in sequence, and stirred evenly to obtain silt-based premixed mortar.
[0041] Example 3 A silt-based premixed mortar, comprising the following raw materials by weight: 220 parts of cement, 530 parts of silt-based admixture, 430 parts of fine aggregate, 14 parts of modified fiber filler, 5.5 parts of activator, 10 parts of high-efficiency water reducer, and 140 parts of water, wherein the fine aggregate is composed of modified fine nickel slag and fine silt powder in a weight ratio of 2:6, the cement is P·O42.5 grade ordinary Portland cement, the high-efficiency water reducer is a polyhydroxy acid-based high-efficiency water reducer with a water reduction rate of 30%, and the activator is prepared by mixing calcium hydroxide and sodium hydroxide in a weight ratio of 4:3; The preparation method of the above-mentioned silt-based premixed mortar comprises the following steps: firstly, according to the mass proportions, cement, modified fiber filler, high-efficiency water reducing agent and water are uniformly mixed, and then silt-based admixtures and fine bones are added in sequence, and stirred evenly to obtain silt-based premixed mortar.
[0042] Comparative Example 1 The same as Example 3, except that an equal amount of the sludge-based admixture prepared in Preparation Comparative Example 2 is used instead of the sludge-based admixture prepared in Preparation Example 2.
[0043] Comparative Example 2 Same as Example 3, except that an equal amount of unmodified carbon fibers (length 3-5 mm) are used instead of the modified fiber filler.
[0044] Comparative Example 3 The same as Example 3, except that an equal amount of unmodified fine nickel slag (continuously graded fine nickel slag with a particle size of 0.075 mm-0.6 mm) is used instead of the modified fine nickel slag.
[0045] Comparative Example 4 The same as Example 3, except that the activator is calcium hydroxide.
[0046] Comparative Example 5 The same as Example 3, except that the activator is sodium hydroxide.
[0047] Performance Testing The silt-based premixed mortar prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was made into test pieces. The test pieces were cubes with a side length of 100 mm. The surfaces were sealed with a polyethylene film and cured at room temperature for 24 hours before demolding. The specimens were moved to a standard curing box and cured to the corresponding age. The following tests were performed. The test results are shown in Table 4.
[0048] The mechanical properties are tested according to the national standard GB / T17671-2021 after the specimens are cured for 28 days; The water retention rate, consistency, frost resistance and setting time are tested in accordance with the national standard GB / T25181-2019 for premixed mortar and the standard JGJ / T70-2009 for basic properties test methods for building mortar.
[0049] Table 4 Performance test Analyzing the data in Table 4, we can see that: 1) The sludge-based premixed mortars prepared in Examples 1 to 3 have good compressive strength, flexural strength, setting time, water retention rate and antifreeze performance. Large-scale processing and high value-added utilization of waste resources such as sea sludge, nickel slag and coal gangue are achieved, and energy conservation, emission reduction and green circular development in the resource process of sea sludge, nickel slag and coal gangue are truly realized, which can effectively reduce the production cost of mortar and is beneficial to environmental protection.
[0050] 2) The comparative analysis of the performance of the silt-based premixed mortars prepared in Example 3 and Comparative Example 1 shows that the volcanic ash activity of the silt powder can be enhanced by sintering the rice husk ash, which is rich in silicon dioxide and aluminum oxide, with the sea silt, thereby improving the overall performance of the silt-based premixed mortar.
[0051] 3) The comparative analysis of the performance of the sludge-based premixed mortars prepared in Example 3 and Comparative Example 2 shows that the surface modification of the modified fiber filler by 3-aminopropyltriethoxysilane and titanium dioxide enhances the interfacial strength between the carbon fibers and other components of the mortar. This enhanced interfacial interaction helps to improve the overall mechanical properties of the mortar, including compressive strength and flexural strength.
[0052] 4) The performance comparison analysis of the sludge-based premixed mortar prepared in combination with Example 3 and Comparative Example 3 shows that the modified fine nickel slag improves the surface properties of the fine nickel slag and improves its compatibility and reactivity with other components of the mortar by spraying the polyacrylic acid emulsion. The polyacrylic acid emulsion has good film-forming and adhesive properties, and can form a thin film on the surface of the fine nickel slag to improve its adhesive properties with cement and other fillers; at the same time, the water absorption and water retention properties of the polyacrylic acid emulsion are conducive to internal maintenance and promote the moisture balance inside the mortar. The workability and setting time of the mortar are improved; at the same time, its enhanced interface strength helps to improve the compressive strength and flexural strength of the mortar.
[0053] 5) The performance comparison analysis of the silt-based premixed mortar prepared in combination with Example 3 and Comparative Examples 4-5 shows that the activator is prepared by mixing calcium hydroxide and sodium hydroxide in a mass ratio of 4:3, and the synergistic effect between calcium hydroxide and sodium hydroxide is utilized, and the complementary effect is: calcium hydroxide mainly provides an alkaline environment to promote the hydration reaction, while sodium hydroxide accelerates the formation of cementitious substances by reacting with silicates in cement. The combination of the two makes the hydration reaction more complete and generates more hydration products. Accelerate the formation of silicates and calcium compounds: Through the synergistic effect of calcium hydroxide and sodium hydroxide, the activator can promote the hydration reaction in cement faster, accelerate the formation of silicates and calcium compounds, and form more hydration products, thereby improving the strength and early hardening speed of concrete. Improve engineering construction efficiency: This synergistic effect helps to shorten the setting time of concrete, reduce waiting time, and improve the overall engineering construction efficiency, which is of great significance for the timely completion and cost control of engineering projects. In summary, the activator prepared by mixing calcium hydroxide and sodium hydroxide in a mass ratio of 4:3 played a key role in the preparation of silt-based premixed mortar. Through its synergistic effect, the performance of the mortar was significantly improved, and the high added value utilization of waste resources such as sea silt, nickel slag and coal gangue was achieved, while reducing production costs and protecting the environment.
[0054] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.
Claims
1. A sludge-based premixed mortar, characterized in that: The preparation raw materials include the following by weight: 200-250 parts of cement, 500-550 parts of sludge-based admixture, 400-450 parts of fine aggregate, 12-15 parts of modified fiber filler, 5-6 parts of activator, 8-12 parts of high-efficiency water reducing agent and 120-150 parts of water.
2. A silt-based premixed mortar according to claim 1, characterized in that: The sludge-based admixture is composed of sludge powder and coal gangue in a mass ratio of 8:2 and is prepared through modification.
3. A sludge-based premixed mortar according to claim 2, characterized in that: The modification method of the sludge-based admixture comprises the following steps: S31, according to the mass parts, put 20 parts of ammonium bicarbonate, 30 parts of ammonium sulfate, 1 part of alkylphenol polyoxyethyl ether and 2 parts of graphene into a ball mill for ball milling, the ball milling speed is 80-100r / min, the ball milling time is 15-20min, and a mixture A is obtained; S32, according to the mass parts, put 800 parts of sludge powder and 200 parts of coal gangue into a ball mill for ball milling, the ball milling speed is 80-100r / min, the ball milling time is 30-40min, and a mixture B is obtained; S33, putting mixture A and mixture B into a ball mill for ball milling, the ball milling speed is 80-100r / min, the ball milling time is 20-25min, and a sludge-based admixture is obtained.
4. A sludge-based premixed mortar according to claim 2, characterized in that: The sludge powder has a particle size of 0.075-2 mm and accounts for 75-85% of the mass fraction; the coal gangue has a particle size of 2-6 mm and accounts for 15-25% of the mass fraction.
5. The silt-based premixed mortar according to claim 2, characterized in that: The method for preparing the sludge powder comprises the following steps: S51. Add 50 parts of sea silt into a stirrer according to the mass fraction, adjust the pH value of the sea silt to 3-4 with 1 mol / L hydrochloric acid solution, then add 18 parts of hydrogen peroxide with a mass concentration of 30%, and then add 80 parts of ferrous sulfate heptahydrate, stir evenly, and react for 10-20 minutes to obtain a mixture A; S52, adjusting the pH value of the mixture A to 6.5-7 using a 3 mol / L NaOH solution, transferring the mixture to a diaphragm plate and frame filter press for filtration until the water content of the sea silt is 55%, thereby obtaining sea silt with a water content of 55%; S53, adding 10 parts by mass of rice husk ash to sea silt having a water content of 55%, stirring evenly and then double-roll crushing to obtain slurry A, and drying slurry A at 100° C. for 6-8 hours to obtain mixture B; S54. According to the mass fraction, mix B is placed in a rotary kiln, pre-sintered at 500°C for 20 minutes, then heated to 900-1000°C, sintered for 3-4 hours, cooled to room temperature, ball-milled and sieved to obtain continuous graded silt powder with a particle size of 0.075-2mm and fine silt powder with a particle size of less than 0.075mm.
6. The silt-based premixed mortar according to claim 1, characterized in that: The fine aggregate is composed of modified fine nickel slag and fine silt powder in a mass ratio of 2:6, and the fine silt powder is the fine silt powder with a particle size less than 0.075 mm prepared according to claim 5.
7. The silt-based premixed mortar according to claim 6, characterized in that: The preparation method of the modified fine nickel slag is as follows: according to the mass fraction, 10 parts of polyacrylic acid emulsion with a solid content of 20% is sprayed onto the surface of 1200 parts of fine nickel slag and stirred for 30-40 minutes, ball milled and sieved to obtain the modified fine nickel slag with a particle size of 0.075 mm-0.6 mm and continuous gradation.
8. The silt-based premixed mortar according to claim 1, characterized in that: The preparation method of the modified fiber filler is as follows: 100 parts of carbon fibers with a length of 3-5 mm and 200 parts of pure water are mixed evenly, the temperature is raised to 35° C., ozone is introduced into the solution at a speed of 3 L / min for 35 minutes, and then the ozone supply is stopped; the solution is sealed, heated to 64° C., and allowed to stand for 4 hours; the solution is stirred for 25 minutes in an open state, 20 parts of 3-aminopropyltriethoxysilane ethanol solution with a mass concentration of 5% is added, the solution is heated to 50° C. and stirred for 50 minutes, and then 10 parts of nano titanium dioxide with a particle size of 50 nanometers is added, stirred for 30 minutes, the nano titanium dioxide is coated on the surface of the carbon fiber, filtered, rinsed with water 3 times, and vacuum dried at 80° C. to obtain the modified fiber filler.
9. The silt-based premixed mortar according to claim 1, characterized in that: The cement is ordinary Portland cement of grade P·O42.5; the high-efficiency water reducer is a polyhydroxy acid-based high-efficiency water reducer with a water reduction rate of 30%; and the activator is prepared by mixing calcium hydroxide and sodium hydroxide in a mass ratio of 4:
3.
10. A method for preparing a sludge-based premixed mortar according to any one of claims 1 to 9, characterized in that: The following steps are involved: According to the mass proportions, cement, modified fiber filler, high-efficiency water reducing agent and water are first mixed evenly, and then silt-based admixtures and fine bones are added in sequence, and stirred evenly to obtain silt-based premixed mortar.
